Suppression of IgE-mediated allergic responses by Rgs13 - Bansal, Geetanjali (2007)
Mast cells provoke allergic responses through degranulation and release of proinflammatory mediators after antigen crosslinking of the high affinity immunoglobulin E (IgE) receptor (FcεRI). Regulator of G protein Signaling (RGS) proteins negatively control G-protein-coupled receptor-mediated signaling through GTPase accelerating protein (GAP) activity. Here, we show that Rgs13 inhibits allergic responses by physically interacting with the regulatory p85α subunit of PI3K in mast cells and disrupting its association with an FcεRI-activated scaffold complex. Rgs13(−/−) mice exhibited increased IgE-mediated mast cell degranulation and anaphylaxis. Thus, apart from its regulation of GPCRs, Rgs13 inhibits immune receptor-induced signalosome assembly in MCs. Abnormal Rgs13 expression or function may underlie some cases of idiopathic anaphylaxis or disorders of amplified MC activity.